2007
DOI: 10.1088/0031-9155/52/8/009
|View full text |Cite
|
Sign up to set email alerts
|

Physical characterization of a high-resolution CCD detector for mammography

Abstract: The physical characteristics of charge-coupled device (CCD) mammography detector with 16-bit dynamic range and 27 microm detector element size were investigated. The detector, with an active area of 1 cm x 20 cm is suitable for slot-scanning systems. We evaluated the detector resolution by measuring the modulation transfer function (MTF) using a tilted edge. We also measured the noise power spectra (NPS) and detective quantum efficiency (DQE) using tungsten spectra filtered with 3 mm Al. We carried out measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Generally, the DQE falls within the range of results reported in the literature for other CMOS and digital mammography detectors. Keeping the differences in measurement setups and conditions in mind, one can tentatively state that the DQE values of the APS and PPS considered in this study are higher than those reported for amorphous silicon flat panels (Vedantham et al 2000), comparable to CCD and CMOS detectors with similar del sizes (Suryanarayanan et al 2005, Tesic et al 1999, Elbakri et al 2007 and lower than that of amorphous selenium flat panels (Saunders et al 2005). A similar statement can be made about the detectors resolution performance.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Generally, the DQE falls within the range of results reported in the literature for other CMOS and digital mammography detectors. Keeping the differences in measurement setups and conditions in mind, one can tentatively state that the DQE values of the APS and PPS considered in this study are higher than those reported for amorphous silicon flat panels (Vedantham et al 2000), comparable to CCD and CMOS detectors with similar del sizes (Suryanarayanan et al 2005, Tesic et al 1999, Elbakri et al 2007 and lower than that of amorphous selenium flat panels (Saunders et al 2005). A similar statement can be made about the detectors resolution performance.…”
Section: Discussionsupporting
confidence: 71%
“…Edge images were dark and gain corrected according to equation (1), and then processed using a MATLAB program developed in house and described elsewhere (Elbakri et al 2007).…”
Section: Modulation Transfer Functionmentioning
confidence: 99%
“…7,[13][14][15] or to max Flat raw ðx; yÞ À Darkðx; yÞ À Á . 16,17 Usually, the scaling factor K is equal to the average over all pixels of the offset-corrected average (over n f frames) reference flat image (i.e., to the first of the three cases in the above list).…”
Section: Introductionmentioning
confidence: 99%
“…raw Flat x y Dark x y − (Elbakri et al, 2007 andElbakri et al, 2009). Usually, the scaling factor K equals to the average value of the offset corrected average reference flat image (first case).…”
Section: Suggested Gain and Offset Correction Algorithmmentioning
confidence: 99%
“…There are several commercial and scientific software packages available to calculate the MTF, NPS and DQE of digital x-ray detectors. A commercial available software package is JDQE (Elbakri, 2010) which is an ImageJ (Rasband, 1997(Rasband, -2011 plugin based on Elbakri's work on x-ray characterization of digital detectors (Elbakri et al, 2006, Elbakri et al, 2007and Elbakri et al, 2009. Two available software packages distributed to researchers and members of the scientific community are MIQuaELa (Ayala et al, 2009) which is a MATLAB-based GUI and OBJ_JQ_reduced (Marshall, 2009c) which is an IDL-based GUI based on Marshall's work (Marshall, 2006a, Marshall, 2006b, Marshall, 2007, Marshall, 2009aand Marshall, 2009b.…”
Section: Validation Of the X-ray Performance Evaluation Algorithmmentioning
confidence: 99%